ANALISIS MINAT BELAJAR SISWA DALAM PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 DI DESA UJUNG BATU BARUS - Rapita Tanjung; Tamin Ritonga; Eva Yanti Siregar (JURNAL MathEdu (Mathematic Education Journal), 2021)
The background of this research is Covid- 19 pandemic in world that caused global health crisis. This problem made a policy to change offline learning to online. Based on the situation, the researcher is interested to highlight the students’ learning interest in Covid-19 period. The approach of the research is descriptive qualitative. Instruments use questionnaire and interview, the informants are the students in Ujung Batu Barus village. The result of the research shows 1) based on questionnaire, 80% students give the answers no interest in learning online and 2) based on interview, students give reasons which included they don’n have Adroid , network that is not smooth, and unable to buy internet quota. It’s concluded 8 from 10 students don’t have interest in learning online.